2004
DOI: 10.1128/jvi.78.5.2627-2631.2004
|View full text |Cite
|
Sign up to set email alerts
|

Binding of the 2F5 Monoclonal Antibody to Native and Fusion-Intermediate Forms of Human Immunodeficiency Virus Type 1 gp41: Implications for Fusion-Inducing Conformational Changes

Abstract: We investigated how the broadly neutralizing monoclonal antibody 2F5 affects the human immunodeficiency virus type 1 envelope glycoprotein as it undergoes receptor-induced conformational changes and show that 2F5 binds both native and fusion-intermediate conformations, suggesting inhibition of a late step in virus entry. We also demonstrate conformational changes in the C heptad of gp41.The envelope glycoprotein (Env) of human immunodeficiency virus type 1 (HIV-1) consists of a surface (gp120) subunit that att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 41 publications
7
71
1
Order By: Relevance
“…The MAb NC-1 was generated by immunizing a mouse with a model gp41 polypeptide from the HIV-1 HXB2 strain, and was shown to bind to the gp41 six-helical bundle of several CXCR4-tropic HIV-1 strains. 48,50 This MAb may be less useful for studying CCR5-tropic HIV-1 envelope glycoproteins, as we found that MAb NC-1 did not detectably interact with the CCR5-using envelope glycoproteins examined in this study.…”
Section: Discussionmentioning
confidence: 60%
“…The MAb NC-1 was generated by immunizing a mouse with a model gp41 polypeptide from the HIV-1 HXB2 strain, and was shown to bind to the gp41 six-helical bundle of several CXCR4-tropic HIV-1 strains. 48,50 This MAb may be less useful for studying CCR5-tropic HIV-1 envelope glycoproteins, as we found that MAb NC-1 did not detectably interact with the CCR5-using envelope glycoproteins examined in this study.…”
Section: Discussionmentioning
confidence: 60%
“…Several reports have provided evidence that 2F5 may target the fusion-intermediate conformation of gp41 (28,29), but previous attempts to mimic the intermediate state have been limited largely to constructs containing only the HR1 and HR2 fragments (9), which could not be used to resolve the issue. In contrast, our gp41-inter constructs contain nearly the full-length gp41 ectodomain, including the full epitopes for 2F5 and 4E10.…”
Section: Stable Conformations Of Hiv Envelope Glycoprotein Gp140 Trimentioning
confidence: 99%
“…Given that mAb 2F5 favorably binds to its epitope in native gp160 and/or transient fusion intermediate state of gp41 [48][49][50], we have constructed three different gp41 variants in a prefusion state and presented these target epitopes in the MPER on the surface of HIV VLP. We report here an immunogenicity study of the VLP/ gp41 variants and the attendant complexities of epitope display and immunodominance observed.…”
Section: Introductionmentioning
confidence: 99%